Neighborhood Social Ties and Shared Expectations for Informal Social Control: Do They Influence Informal Social Control Actions? - Wickes, Rebecca (Journal of quantitative criminology, 2017)
Objectives Social disorganization states that neighborhood social ties and shared expectations for informal social control are necessary for the exercise of informal social control actions. Yet this association is largely assumed rather than empirically examined in the literature. This paper examines the relationship between neighborhood social ties, shared expectations for informal social control and actual parochial and public informal social control actions taken by residents in response to big neighborhood problems. Methods Using multi-level logistic regression models, we integrate Australian Bureau of Statistics census data with the Australian Community Capacity Study survey data of 1310 residents reporting 2614 significant neighborhood problems across 148 neighborhoods to examine specific informal social control actions taken by residents when faced with neighborhood problems. Results We do not find a relationship between shared expectations for informal social control and residents’ informal social control actions. Individual social ties, however, do lead to an increase in informal social control actions in response to ‘big’ neighborhood problems. Residents with strong ties are more likely to engage in public and parochial informal social control actions than those individuals who lack social ties. Yet individuals living in neighborhoods with high levels of social ties are only moderately more likely to engage in parochial informal social control action than those living in areas where these ties are not present. Shared expectations for informal social control are not associated with the likelihood that residents engage in informal social control actions when faced with a significant neighborhood problem. Conclusion Neighborhood social ties and shared expectations for informal social control are not unilaterally necessary for the exercise of informal social control actions. Our results challenge contemporary articulations of social disorganization theory that assume that the availability of neighborhood social ties or expectations for action are associated with residents actually doing something to exercise of informal social control.